Facing Neonatal Stenotrophomonas Maltophilia Infection: TrimethoprimSulfamethoxazole or Levofloxacin? - Toktam Faghihi (Journal of Pharmaceutical Care, 2019)
Stenotrophomonas maltophilia, a multidrug-resistant gram-negative bacillus is an opportunistic organism. Infections caused by this pathogens needs to be treated promptly and is life-threatening in neonates (1,2). The most common clinical presentations are pneumonia and bacteremia. Treatment includes limited number of antimicrobials with defined MIC cutoffs by US Clinical and Laboratory Standards Institute (CSLI). These include trimethoprim-sulfamethoxazole (TMP-SMX), levofloxacin, ticarcillin-clavulanate, minocycline, ceftazidime and chloramphenicol (1). Treatment of choice is TMP-SMX based on reliable in-vitro activity and favorable clinical outcomes (1, 2). Levofloxacin is a potential alternative to TMP-SMX (1). Usually we encounter high resistant rates to ceftazidime (3). Ticarcillin-clavulanate is not readily available in Iran.  Also it is shown to be less active than TMP-SMX in vivo (2).